2017
DOI: 10.1108/qrfm-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes financing gap in Indian SMEs – owners’ perspective?

Abstract: PurposeThis exploratory study aims to investigate the financing issues faced by Indian small and medium enterprise (SME) owners. It also classifies the financing constraints into four financing gaps, namely, demand, knowledge, supply and benevolence. Design/methodology/approachThe study uses the convergent interviewing technique to highlight the key issues being faced by SME owners in financing. Forty-four owners from different industries and having dispersed demographics have been interviewed in the study. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
0
30
0
4
Order By: Relevance
“…Qualitative research methods based on in-depth interviews were used for this study. Interviews are often used to gather detailed insights from specific individuals about a new issue (Rao et al, 2017). In-depth interviews are particularly valuable when dealing with vulnerable groups such as those with a disability (Liamputtong, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research methods based on in-depth interviews were used for this study. Interviews are often used to gather detailed insights from specific individuals about a new issue (Rao et al, 2017). In-depth interviews are particularly valuable when dealing with vulnerable groups such as those with a disability (Liamputtong, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Open questioning gave claimants freedom to respond in their own way and with as much detail as they wanted (Rao et al, 2017). Toward the end of their interview, each interviewee was invited to offer suggestions/changes which may be helpful to the TPD claims process.…”
Section: Data Collectionmentioning
confidence: 99%
“…Also, the limitation of financial resources further reduces the survival possibilities for MSMEs (Heckmann et al, 2009;Singh and Kaur, 2019). Other than operational-financial constraints, scholars have confirmed that financing issues, credit gap, insolvency and bankruptcy negatively affect the survival probabilities of small firms (Awasthi, 2011;Yadav, 2012;Nag and Das, 2015;Gautami, 2018;Sekhar and Radha, 2019;Rao et al, 2017;Bansal et al, 2019).…”
Section: Financial Constraints Faced By Msmesmentioning
confidence: 99%
“…Since MSMEs are not able to compete with the large enterprises due to constrained cash inflows and savings, the accessibility to outside credit becomes significantly low for smaller firms (Laxmi and Kumar, 1999;Osei-Assibey et al, 2012;Yadav and Tripathi, 2018). The difficulty in obtaining formal finance is preoccupied with issues such as easiness, availability, flexibility and affordability; therefore, most firms remain seriously constrained or resort to unorthodox means of financing (Neeley, 2004;Rao et al, 2017).…”
Section: Financing Constraints and Cash Flow Constraintsmentioning
confidence: 99%
“…There is a tendency for lenders to withhold information from their clients. Extant studies (Yen et al, 2019;Ol ah et al, 2019;Haniff et al, 2017;Rao et al, 2017;Bbenkele, 2007) report owner-manager complaint about lack of transparency in credit granting contract with FIs. Lenders have often relied on their previous experience and transactions with SMEs in setting credit granting criteria.…”
mentioning
confidence: 99%